2020
DOI: 10.3390/math8122177
|View full text |Cite
|
Sign up to set email alerts
|

A Simple-FSDT-Based Isogeometric Method for Piezoelectric Functionally Graded Plates

Abstract: An efficient isogeometric analysis method (IGA) based on a simple first-order shear deformation theory is presented to study free vibration, static bending response, dynamic response, and active control of functionally graded plates (FGPs) integrated with piezoelectric layers. Based on the neutral surface, isogeometric finite element motion equations of piezoelectric functionally graded plates (PFGPs) are derived using the linear piezoelectric constitutive equation and Hamilton’s principle. The convergence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…In the literature various numerical methods were combined for predicting the behaviors of FGM plates. A broad review of them is presented (e.g., in Refs [17,18]). The authors of Refs [17,18] proposed novel numerical methods for the analysis of FGM and piezoelectric FGM structure (square plates, skew plates, and toruses).…”
Section: Methods Of the Solutionmentioning
confidence: 99%
“…In the literature various numerical methods were combined for predicting the behaviors of FGM plates. A broad review of them is presented (e.g., in Refs [17,18]). The authors of Refs [17,18] proposed novel numerical methods for the analysis of FGM and piezoelectric FGM structure (square plates, skew plates, and toruses).…”
Section: Methods Of the Solutionmentioning
confidence: 99%
“…By converging unmanned aerial vehicles, the expected handiwork creates new fields of inquiry [42]. A Simple-FSDT-based iso-geometric approach with the mathematical expression for piezoelectric functionally graded plates has been studied on vibration analysis [43]. Such studies have been found to shape the control of the antenna reflector to the desired shape-a closed-loop iteration based on the influence coefficient matrix and FE model [44].…”
Section: Vibration Controlmentioning
confidence: 99%
“…Using the simple FSDT (which involves four displacement functions) to model the mechanical displacement of a sandwich plate, in addition to assuming a linearly varying electric potential along the thickness and neglecting the electric field in in-plane directions, Liu et al [38] adopted an isogeometric analysis method to analyze the free vibration, static bending, and dynamic vibration control of sandwich rectangular plates. Rouzegar and Abad [39] proposed a Navy-type solution for a sandwich rectangular plate by using the refined four-variable plate theory to model mechanical displacement and assuming a quadratic electric potential distribution along the thickness direction.…”
Section: Introductionmentioning
confidence: 99%